Safety of Oral Dofetilide Reloading for Treatment of Atrial Arrhythmias. (October 2017) - Cho, Jae Hyung; Youn, So Jin; Moore, JoEllyn C.; Kyriakakis, Roxanne; Vekstein, Carolyn; Militello, Michael; Poe, Stacy M.; Wolski, Kathy; Tchou, Patrick J.; Varma, Niraj; Niebauer, Mark J.; Bhargava, Mandeep; et al.
Abstract : Background: Although dofetilide labeling states that the drug must be initiated or reinitiated with continuous electrocardiographic monitoring and in the presence of trained personnel, the risks of dofetilide reloading justifying repeat hospitalization have not been investigated. Methods and Results: Patients admitted for dofetilide reloading for atrial arrhythmias were retrospectively reviewed. The need for dose adjustment and the incidence of torsades de pointes (TdP) were identified. The incidence of TdP in dofetilide reloading was compared with patients admitted for dofetilide initial loading. Of 138 patients admitted for dofetilide reloading for atrial arrhythmias, 102 were reloaded at a previously tolerated dose, 30 with a higher dose from a previously tolerated dose and 2 at a lower dose; prior dosage was unknown in 4 patients. Dose adjustment or discontinuation was required in 44 patients (31.9%). No TdP occurred in the same dose reloading group, but TdP occurred in 2 patients admitted to increase dofetilide dosage (0% versus 6.7%; P =0.050). Dofetilide dose adjustment or discontinuation was required in 30 of 102 patients (29.4%) reloaded at a previously tolerated dose and in 11 of 30 patients (36.7%) admitted for an increase in dose. Conclusions: Although no TdP occurred in patients admitted to reload dofetilide at the same dose as previously tolerated, dosage adjustments or discontinuation was frequent and support the need for hospitalization for dofetilide reloading. Patients admitted for reloading with a higher dose tended to be at higher risk for TdP than patients reloaded at a prior tolerated dose.